Predictive Validity of a Student Self-Report Screener of Behavioral and Emotional Risk in an Urban High School. Issue 4 (1st December 2016) - Dowdy, Erin; Harrell-Williams, Leigh; Dever, Bridget V.; Furlong, Michael J.; Moore, Stephanie; Raines, Tara; Kamphaus, Randy W.
Abstract: Increasingly, schools are implementing school-based screening for risk of behavioral and emotional problems; hence, foundational evidence supporting the predictive validity of screening instruments is important to assess. This study examined the predictive validity of the Behavior Assessment System for Children-2 Behavioral and Emotional Screening System Student Form (BESS Student) in the authentic context of an urban high school that conducted universal screening over 3 years. Multivariate regression, sensitivity, specificity, and receiver operating characteristic curve analyses were used to examine the BESS Student scores' prediction of internalizing symptoms. BESS Student scores were able to explain a significant proportion of the variance in internalizing symptoms concurrently, but predictive validity estimates decreased over time. Significant gender differences were present; BESS Student scores were better able to predict internalizing symptoms for females. Implications for research and practice involving screening for behavioral and emotional problems are discussed.